The presence of refugia and population of insect pest in rice field. Issue 2 (July 2021) - Aminah, S N; Nasruddin, A; Annisaa, N W; Abdullah, T; Fatahuddin,
Abstract: Refugia is a type of plant playing the role as a food source and shelter for natural enemies in extreme environmental conditions. Legumes, food plants and flowering plants are used as refugia. The purpose of the research is to study the dominant pest population in the embankment of rice fields planted with refugia. The research was conducted in Tanasitolo village, South Sulawesi from June to November 2017. The study used a Randomized Block Design of five treatments and repeated it four times. The research was started by planting several different plants as refugia in the embankment of rice fields, namely: P0 = embankment without plant (control); P1 = maize and soybean in embankment; P2 = flowering plants in embankment; P3 = taro and banana in embankment; and P4 = long beans in embankment. The results showed that rice fields used various plants as refugia, the insect population was in the lowest number. The results showed that Valanga sp. were not found in P1 when the rice was 56 and 63 days after planting. The number of Nephotettix virescens (0.5 individuals) when the rice was 42 days after planting. Leptocorisa acuta has the lowest population at P1 and P3 in the age 84 days after planting (10.5 individuals). The conclusion of the experiment is the lowest population of grasshopper L. migratoria in rice age 56 and 63 days after planting was showed P1 (maize and soybean). The lowest population of green leafhopper N. virescens in the rice age 42 days after planting showed in the treatment P1 (maize and soybean). In the rice age in the 84 days after planting with treatment P1 (maize and soybean) and P3 (taro and bananas) showed a very low population.